Дешифрування гіперспектральної космічної інформації на основі текстурних і спектральних характеристик досліджуваних об’єктів - Якимчук, В. Г.; Суханов, К.Ю.; Козлов, З.В.; Ліщенко, Л.П. (Видавничий дім "Академперіодика" НАН України, 2008)
The interpretation of hyperspectral space images based on the textural and spectral characteristics of studied objects is examined. It is suggested to perform the interpretation using a spectral shift function along the electromagnetic radiation wavelength as an integral indicator of the spectral characteristics of urbanlandscape elements.